Economic development : a regional, institutional, and historical approach - Grabowski, Richard, 1949- (M.E. Sharpe, 2007)
Provides an introduction to economic development in both an historical and contemporary, comparative, and systems framework. This volume authors analyzes the development process within the historical context of each region, and considers institutional inheritance from both the pre-colonial and colonial eras and in contemporary times.